Ethical Code Enforcement of the Indonesian National Police on Sexual Orientation Deviation - Arnapi; Karnaji; Raharja, Gede Dimas Bayu Hardi; Sofia, Arijna Nurin (Arena Hukum, 2025)
The Indonesian National Police (Polri) has the task of maintaining public order in overcoming problems of social deviation, such as sexual orientation deviation (Lesbian, Gay, Bisexual, and Transgender/LGBT). Social deviation in the Polri is limited by norms, rules, and standards of behaviour regulated by the Indonesian Police Code of Ethics (KEPP). This normative legal research analyses regulation of sexual orientation deviation in the KEPP and the enforcement of the code of ethics for sexual orientation deviation by Polri members. The author tries to find a common thread between rules, theories, and practices in compiling the KEPP concept bydeveloping previous research by Mallory et al. (2013), Faridah (2019) and Puspita (2016). Unlike the United States, which protects LGBT rights in the police organization, this is undoubtedly motivated by culture. This study shows : 1) a legal vacuum where sexual orientation deviation in the form of LGBT needs to be included in the violation of the Police’s standard of conduct in Indonesia so that the interpretation of deviation is still interpreted broadly, so deregulation is needed to realize legal reform that upholds religion and morals; also 2) the views of natural law and Human Rights on the regulation of sexual orientation deviation based on KEPP and howthe concept of imposing sanctions for the code of professional ethics if an officials and member of the Police is proven to be LGBT. This paper offers comparative insight for jurisdictions grappling with similar ethical dilemmas within law enforcement institutions in religiousconservative societies.